Nonlinear structural and vibration analysis of straddle monorail pantograph under random excitations - Sun Wenjie; Tang Xiaobin (Nonlinear Engineering)
The dynamic behavior of the straddle monorail pantograph system is significantly influenced by nonlinearities arising from its unique structural configuration and operational environment. This article presents a mathematical model that incorporates both nonlinear geometric and material properties of the pantograph. A finite element model is utilized to perform modal and static analyses, identifying stress concentrations and dynamic characteristics. To account for random vibration excitations, a nonlinear dynamic response framework is developed, considering vehicle-induced vibrations and network irregularities as stochastic excitation sources. The results demonstrate that these nonlinearities amplify specific resonances under random excitation, leading to increased stress and deformation at critical points. These findings provide a foundation for enhancing fault detection strategies and designing more robust pantographs, with nonlinear vibration monitoring proposed as an effective diagnostic tool. This study contributes to both theoretical understanding and practical improvements in ensuring the reliability and longevity of straddle monorail systems.